Linking Transcriptional Dynamics of Peat Microbiomes to Methane Fluxes during a Summer Drought in Two Rewetted Fens - Wang, Haitao; Jurasinski, Gerald; Täumer, Jana; Kuß, Andreas W.; Groß, Verena; Köhn, Daniel; Günther, Anke; Urich, Tim (Environmental science & technology, 2023)
Rewetted peatlands are reestablished hot spots for CH4 emissions, which are subject to increased drought events in the course of climate change. However, the dynamics of soil methane-cycling microbiomes in rewetted peatlands during summer drought are still poorly characterized. Using a quantitative metatranscriptomic approach, we investigated the changes in the transcript abundances of methanogen and methanotroph rRNA, as well as mcrA and pmoA mRNA before, during, and after the 2018 summer drought in a coastal and a percolation fen in northern Germany. Drought changed the community structure of methane-cycling microbiomes and decreased the CH4 fluxes as well as the rRNA and mRNA transcript abundances of methanogens and methanotrophs, but they showed no recovery or increase after the drought ended. The rRNA transcript abundance of methanogens was not correlated with CH4 fluxes in both fens. In the percolation fen, however, the mcrA transcript abundance showed a positive and significant correlation with CH4 fluxes. Importantly, when integrating pmoA abundance, a stronger correlation was observed between CH4 fluxes and mcrA/pmoA, suggesting that relationships between methanogens and methanotrophs are the key determinant of CH4 turnover. Our study provides a comprehensive understanding of the methane-cycling microbiome feedbacks to drought events in rewetted peatlands.